Digital Transformation in Distance Learning: Problems and Challenges During COVID-19 Pandemic: Sidra Noreen, Norman Reid (PJDOL, 2021)
Abstract COVID-19 has affected universities in many countries as face-toface contacts were reduced to minimize virus transmission. It has required universities to move to online teaching and learning mode which caused diverse challenges. This study looks at the key problems and challenges as seen by both learners and academics of the Allama Iqbal Open University. For this purpose, 20 learners and 12 academics from the Faculty of Education were selected through purposive sampling technique. Qualitative data were gathered through focus group discussions and interviews. Thematic analysis was used to generate themes and codes. The major findings are that there is a lack of access to digital technology and reliable internet connectivity, especially for learners from rural areas. Both academics and learners lack experience in how to use the new technologies. Much of the software is insufficiently user-friendly with a lack of support offered. The study concludes that the effectiveness of rapidly growing digital learning will be greatly limited until these key challenges are addressed. Keywords: digital learning, problems and challenges, distance learning, COVID-19